Pengaruh Media Sosial Terhadap Pola Komunikasi SMA Muhammadiyah Maumere Diera Digital - Maria Roslinda; Nurmala Hasan; Maria Martika; Salsabilah A. Fernanda; Ra'is Abin; Veronika Erlina Deso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Social media provides various ways of communicating that are short but easy to understand and very fast in the global, this allows students of SMA Muhammadiyah Maumere to easily connect with peers and family in various parts of the world easily. This study shows that there are still many shortcomings in understanding the negative impacts of social media use, such as reduced family interaction and increased risk of negative behavior among the younger generation. Therefore, research using a systematic approach in reviewing the literature needs to be focused on identifying effective strategies to overcome the negative impacts of social media, as well as exploring the potential of social media as a positive tool to strengthen interpersonal relationships among the Generation. The main objective of this study is to provide a comprehensive understanding of the influence of social media on communication patterns and social relationships of the Generation, as well as identify strategies that can help them manage their use of social media in a healthier and more productive way. This study uses a qualitative research method with a descriptive research type. The findings are that most teenagers at SMA Muhammadiyah Maumere have Facebook, WhatsApp, Messenger, Instagram and online game accounts to interact and communicate with others. The use of social media as a place to find friends and information. One form of media from social media is the formation of networks between teenagers. The network that is built does not only expand friendships or followers in cyberspace, but must also be built with interactions between teenagers. Interactions that occur on social media are in the form of commenting on each other or giving likes. The implications of the research are that social media can have positive and negative effects.or giving likes. The implications of the study are that social media can have positive and negative effects.